"Education just a game when you can play Indians [sic] or Eskimos [sic] with Museum exhibits" (Philadelphia Evening Bulletin, 1942)
Marianne Golden, Helen Ehrline, Elizabeth Whyte, Charles Fisher, Dorothy Reynolds, Dorothy Batty and Lloyd Erdman from the Frankford Friends School visit the University of Pennsylvania Museum of Archaeology and Anthropology. Title from clipping caption